DEVELOPMENT OF A NEW DOSAGE FORM WITH POTENTIAL ANTIBURN EFFECT ON THE MODEL OF THERMAL INJURIES IN RATS - Valivodz, Iryna; Borysiuk, Iryna; Molodan, Yulia (European Science, 2025)
Literature data on the prevalence, etiology, pathogenesis and modern methods of burn disease therapy were analyzed and systematized. Particular attention is paid to the use of medicinal plants and biologically active compounds in the treatment of burn in